Oyu Tolgoi and Rio Tinto partnership with Palantir Technologies to provide effective geotechnical risk management - Moorcroft, T.H.; Simanjuntak, K.; Dorjsuren, O.; Sanaakhorol, M.; Enkhtaivan, E.; Watt, G.; Eickhoff, V.; Cerny, L.; Deasy, C.; Zimmermann, T. (Caving 2022: Proceedings of the Fifth International Conference on Block and Sublevel Caving, 2022)
Oyu Tolgoi, a copper and gold mine in Mongolia, is one of the deepest and largest block cave mines in the world. The depth and size, combined with demanding rock conditions, brings new technical and operational challenges in providing effective geotechnical risk management. At Oyu Tolgoi, Rio Tinto has partnered with Palantir Technologies, the enterprise software company, to support geotechnical risk management. This paper describes how effective geotechnical risk management practices are facilitated through a datadriven operations platform that connects data, analytics, and business teams to a common foundation. Through data integration, and a strong data foundation, Oyu Tolgoi engineers can monitor and act upon the mine’s aggregated data asset against their trigger action response plans and production data with cave management plan rules. Data-driven cave monitoring workflows improve visibility into operations at the cave, support incident prevention, provide transparency for optimal collaboration between geotechnical and production engineers and inform decisions on cave construction sequencing and draw strategy. This amounts to a new and stronger footing from which to provide effective geotechnical risk management.